Dynamic Nanohybrid-Polysaccharide Hydrogels for Soft Wearable Strain Sensing - Pejman Heidarian; Hossein Yousefi; Akif Kaynak; Mariana Paulino; Saleh Gharaie; Russell J. Varley; Abbas Z. Kouzani (Sensors, 2021)
Electroconductive hydrogels with stimuli-free self-healing and self-recovery (SELF) properties and high mechanical strength for wearable strain sensors is an area of intensive research activity at the moment. Most electroconductive hydrogels, however, consist of static bonds for mechanical strength and dynamic bonds for SELF performance, presenting a challenge to improve both properties into one single hydrogel. An alternative strategy to successfully incorporate both properties into one system is via the use of stiff or rigid, yet dynamic nano-materials. In this work, a nano-hybrid modifier derived from nano-chitin coated with ferric ions and tannic acid (TA/Fe@ChNFs) is blended into a starch/polyvinyl alcohol/polyacrylic acid (St/PVA/PAA) hydrogel. It is hypothesized that the TA/Fe@ChNFs nanohybrid imparts both mechanical strength and stimuli-free SELF properties to the hydrogel via dynamic catecholato-metal coordination bonds. Additionally, the catechol groups of TA provide mussel-inspired adhesion properties to the hydrogel. Due to its electroconductivity, toughness, stimuli-free SELF properties, and self-adhesiveness, a prototype soft wearable strain sensor is created using this hydrogel and subsequently tested.